Education for Muslim girls in contemporary Britain: social and political dimensions - Haw, Kaye (1995)
This research examines how the discourses of gender, 'race ', culture and religion are articulated in the educational experiences of Muslim girls. Using the data collected in a private Muslim girls' school (old Town High) and a single-sex state school with a high proportion of Muslim girls (City State) it critically examines how stereotypical representations may come to constitute a commonsense understanding of Muslim women and how these representations can exercise an important influence in shaping teacher perceptions about the presumed needs of their Muslim students.